The effects of bullying behaviours among nursing students in Sierra Leone: a qualitative exploratory study - Jedidah Olayinka Johnson; Suzanna Anwagwa; Francess Yaata Kamara (BMC Nursing)
Abstract Background Bullying can have profound negative effects on nursing students who often contend with psychological trauma because of repeated acts of mistreatment. This study was done to explore the effects of bullying behaviours among nursing students with above average and below average academic performance in two nursing schools in Sierra Leone. Methods A qualitative exploratory study involved six rounds of data collection and analysis over a one month period. 48 nursing students recruited from Njala University School of Nursing and Mattru School of Nursing participated in semi structured interviews. Recruitment was done using a purposive sampling method and students with higher than average and lower than average Grade point average (GPA) were selected to participate in the interviews. Interviews were audiotaped recorded and transcribed verbatim for analysis. An inductive approach with line-by-line coding to identify themes and subthemes was done for the first set of interviews, following this the researchers took a deductive approach to analysis to evaluate if subsequent themes were consistent with initial analysis. Results Sensitization and apathy were the two broad themes regarding the effects of bullying behaviour demonstrated by students with higher than average and lower than average GPA respectively. Both groups of students had come to accept the inevitability of bullying as nursing students despite the distress it caused them. However, students with lower-than-average GPA also demonstrated resentment and a loss of interest in their studies because of the bullying they had encountered. Conclusion The findings of this study demonstrate that bullying negative affects nursing students regardless of their academic performance. There is an urgent need for policy makers to prioritise the deterrence of bullying of nursing students through implementation of strategies that protect students and punish perpetrators of abuse in nursing schools nationwide.